PROVISIONS CONCERNING THE ORGANIZATION OF EVENTS FOR THE PROMOTION OF PRODUCTS ON PHARMACEUTICAL MARKET IN ROMANIA - IOSIF, Alina Natalia; GURGU, Elena (Annals of Spiru Haret University. Economic Series, 2019)
For the purpose of writing this paper, we were motivated to choose this subject as it is a core part of the pharmaceutical companies' business strategy of promoting medicines. Regarding the importance of the research theme and the business environment, it is crucial that anyone connected to this business should realize the importance of organization, details, good deployment and impact of each event. In this respect, marketing can be seen as a true system of economic activities related to the programming of products and services that have the role of satisfying the requirements of current and potential consumers considerably, but is also linked to prices, promotion and distribution products or services. Having knowledges about how important is the marketing part of pharmaceutical market, taking in consideration the huge budgets that medical and pharmaceutical companies spend on the events organized in this domain, we consider that a company which is able to have a new approach and a new vision for the organization of events and sharing medical education to doctors and medical information to patients will have a big success.